Nutrition Education and Training on Making Tempeh-Carrot Nuggets as a High-Protein Snack for Students of State Elementary School 011 Sekupang Batam - Miratia Afriani; Eryd Saputra; Heri Nuryanto (PUSLITABMAS-Politeknik Pariwisata Batamc, 2026)
This Community Service Program aimed to improve nutritional knowledge and healthy food processing skills among students of State Elementary School 011 Sekupang Batam through nutrition education and training in making tempeh-carrot nuggets as a high-protein snack. The program was conducted using educational sessions, demonstrations, and hands-on practice involving elementary school students as participants. The educational materials covered the importance of balanced nutrition, the role of protein in children's growth and development, and the nutritional benefits of tempeh and carrots. Following the educational session, participants took part in a practical training activity on preparing tempeh-carrot nuggets, from ingredient preparation to product serving. The results indicated that students showed high enthusiasm throughout the activity and demonstrated improved understanding of the importance of consuming nutritious foods. The tempeh-carrot nuggets produced during the training were well accepted by the participants due to their appealing taste and nutritional value. This activity demonstrates that the integration of nutrition education and food processing practice can be an effective strategy for enhancing knowledge and promoting healthy snacking habits among school-aged children.